Using of the Waterfall Model in the Development of Herbal Medicine Sales Information System - Hidayati, Nur (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
The increasingly advanced development of technology is currently a challenge for companies to create and develop information systems that are implemented in the company. The use of computers equipped with application programs can help improve company performance, such as in trading companies. Where the sales sector has an important role in increasing the progress of the company, because it is related to the income that the company can obtain. Besides that, sales is also directly related to customers, where good service is very necessary to create customer satisfaction. Therefore, it is necessary to implement a good information system for the sales information system. However, looking at current conditions, there are still many companies or places of business where data processing is still done traditionally. If this continues, it can cause problems that can be detrimental to the company. As for problems that arise, such as data processing which still uses handwriting, this is very prone to recording errors. Besides that, it often happens that sales reports are created that are not the same as existing transactions. These problems should be resolved immediately, by developing the information system. So that companies can survive amidst the current competition. In solving the problem, the right method is needed, such as using the Waterfall model. Where this model is carried out in stages and sequentially. By using the right model, the right program application can be produced, according to what the company needs. So that problems that arise can be resolved well, customers get satisfaction from the services provided and company profits increase.